1996
DOI: 10.1046/j.1365-313x.1996.9050715.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollination induces mRNA poly(A) tail‐shortening and cell deterioration in flower transmitting tissue

Abstract: SummaryPollination induces many physiological responses in the flower, including deterioration and death in specific pistil cell types. It is shown here that within the style of tobacco, pollination-induced cell deterioration was restricted to the transmitting tissue while the surrounding cortical tissue was not affected. It was distinct from general senescence since exogenously applying the senescence-inducing hormone ethylene, or its precursor aminocyclopropane-1-carboxylic acid (ACC), to the flower or the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 61 publications
1
75
0
1
Order By: Relevance
“…Expression of GFP-Rab11b(DN) or GFP-Rab11b(CA) Inhibits Pollen Tube Growth in Vivo and Reduces Male Fertility Upon pollination on the stigma, wild-type tobacco pollen grains germinate efficiently, and a majority of their tubes reach the styleovary junction ;30 h after pollination (Cheung et al, 1995;Wang et al, 1996). Direct examination of pollinated pistils ( Figures 6A to 6N) showed that most GFP-expressing (data not shown) and GFP-Rab11b-expressing grains germinated ( Figure 6A), and many of these tubes reached the basal stylar region by 30 h after pollination ( Figure 6C).…”
Section: Expression Of Gfp-rab11b(dn) and Gfp-rab11b(ca) Inhibits In mentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of GFP-Rab11b(DN) or GFP-Rab11b(CA) Inhibits Pollen Tube Growth in Vivo and Reduces Male Fertility Upon pollination on the stigma, wild-type tobacco pollen grains germinate efficiently, and a majority of their tubes reach the styleovary junction ;30 h after pollination (Cheung et al, 1995;Wang et al, 1996). Direct examination of pollinated pistils ( Figures 6A to 6N) showed that most GFP-expressing (data not shown) and GFP-Rab11b-expressing grains germinated ( Figure 6A), and many of these tubes reached the basal stylar region by 30 h after pollination ( Figure 6C).…”
Section: Expression Of Gfp-rab11b(dn) and Gfp-rab11b(ca) Inhibits In mentioning
confidence: 99%
“…RNA and protein isolation and gel blot analyses followed previous procedures (Wang et al, 1993(Wang et al, , 1996, except that chemiluminescent detection was used for some of the protein blots.…”
Section: Rna and Protein Analysesmentioning
confidence: 99%
“…In addition, DNA ladders were observed during cell death in toxin-treated tomato protoplasts and leaflets, and the intensity of the DNA ladders was inhibited by Zn 2+ [30]. Moreover, certain levels of Zn 2+ inhibit the PCD induced by various stresses on the plant cell [30]. Our research indicated that the change of Zn 2+ accumulation may affect the expression of BEN1-LIKE protein.…”
Section: Acta Biologica Hungarica 66 2015mentioning
confidence: 61%
“…It has been shown that Zn 2+ has a significant impact on apoptosis of plant cells [12][13]30]. We investigated the dynamic change of Zn 2+ accumulation in the development of MSEs (Fig.…”
Section: Acta Biologica Hungarica 66 2015mentioning
confidence: 99%
See 1 more Smart Citation